1988
DOI: 10.1203/00006450-198807000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Colonic Sodium Transport during Ontogeny: Loss of an Amiloride-Sensitive Sodium Pathway

Abstract: ABSTRACT. Net colonic sodium and fluid absorption is higher in suckling and weanling rats than in adult rats. This study was undertaken to investigate the mechanisms behind these differences. In vivo perfusion of the colon was performed in 14-to 80-day-old rats. Net Na and water uptake decreased exponentially from 14 to 80 days of age. Na uptake was 402 f 73 pgEq/min/g DT in 20-day-old rats and 116 f 6 pEq/min/g DT in 40-day-old rats. After amiloride treatment, net Na transport was reversed to net secretion (-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Several studies have provided strong evidence that aldosterone increases Na + absorption in the adult rat distal colon by inhibiting electroneutral Na + /H + exchange and inducing electrogenic Na + absorption via Na + channels (Binder et al 1991). Even if Na + absorption is increased and electrogenic amiloride-sensitive Na + transport pathway dominates in the immature rat distal colon (Pácha et al 1987;Finkel et al 1988), we have not observed any parallel changes in aSCC, plasma level of aldosterone or apical membrane area. This means that the incorporation of Na + channels into the apical membrane occurs without any increase in the membrane domain and that the regulation of the Na + pathway in the immature rat distal colon by aldosterone is localized predominantly in the apical membrane without any significant correlation between its ultrastructure and Na + transport.…”
Section: Groupcontrasting
confidence: 73%
See 2 more Smart Citations
“…Several studies have provided strong evidence that aldosterone increases Na + absorption in the adult rat distal colon by inhibiting electroneutral Na + /H + exchange and inducing electrogenic Na + absorption via Na + channels (Binder et al 1991). Even if Na + absorption is increased and electrogenic amiloride-sensitive Na + transport pathway dominates in the immature rat distal colon (Pácha et al 1987;Finkel et al 1988), we have not observed any parallel changes in aSCC, plasma level of aldosterone or apical membrane area. This means that the incorporation of Na + channels into the apical membrane occurs without any increase in the membrane domain and that the regulation of the Na + pathway in the immature rat distal colon by aldosterone is localized predominantly in the apical membrane without any significant correlation between its ultrastructure and Na + transport.…”
Section: Groupcontrasting
confidence: 73%
“…Since the absorptive capacity and basolateral or apical cell membrane surface areas are related in the large intestine (Kashgarian et al 1980;Elbrond et al 1991), we posed the question of whether such a relationship also exists during the developmental period of rapidly changing colonic absorption (Finkel et al 1988;. Our principal finding is that the basolateral but not apical membrane area increases markedly during weaning and that the morphological changes correlate well with the observed functional changes.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…High Na + absorption in the neonatal period and the reduced Na + absorption in postnatal life are observed in the colon of rat, rabbit, and human (86, 132, 216), and also in the rat small intestine (227). The Na + absorptive pathway in the colon is mainly mediated by amiloride-sensitive Na + channels (216, 228, 229).…”
Section: Small Intestinal Na+/h+ Exchangementioning
confidence: 99%
“…We believe that the change in effect of amiloride during postnatal development in the sheep is more likely to reflect the progressive acquisition of an alternative pathway for Na+ that is insensitive to the presence of amiloride. It is of interest in this respect that the colon of the rat displays developmental changes in an amiloridesensitive sodium pathway (Finkel, Eklof & Aperia, 1988) that are similar to those in the sheep lung. At 20 days of postnatal life amiloride completely blocked net sodium absorption from the lumen of the rat colon yet by 40 days of life it had no effect at all although sodium absorption was still present (albeit at a lower rate).…”
Section: Mechanisms Of Liquid Absorptionmentioning
confidence: 99%